Development, Installation, and Data Analysis for a Scanning VLF Research Receiver Employed at the Air Force Geopole Observatory, Thule, Greenland. - Oelbermann,Ernest J.; Smitley,Charles R. (1972)
The report summarizes research and development connected with the use of a scanning VLF receiver at Thule, Greenland, to study polar cap disturbances during PCA's. The report describes the equipment, the quiet-day solar controlled patterns of a number of polar path VLF circuits, and VLF amplitude perturbations produced by solar proton events which occurred on September 1, October 3, and December 2, 1971. It is concluded that the VLFamplitude data are very sensitive and can be used to provide detection and tracking information on the movement of PCA centers across the polar cap. It is recommended that the scanned bandwidth be reduced and the sweep rate speeded up to shorten dead time and improve the time resolution of the system. (Author)